Antioxidant Capacity of Black Tea Obtained Using Tyrosinase and Tannase Treatment - Fiyan Maulana Rajendra; Rachmad Gunadi; Supriyadi Supriyadi (Indonesian Food and Nutrition Progress, 2023)
Black tea has a lower antioxidant capacity than other teas, such as green tea, white tea, and oolong tea. Tannase and tyrosinase can be used as a treatment to improve the quality of black tea infusion. Tannase has been reported to be an effective way to enhance antioxidant activity in black tea infusion. Meanwhile, tyrosinase could produce higher theaflavin content than thearubigin. Research about Ready-to-Drink (RTD) black tea preparation with the addition of tannase and tyrosinase to fresh tea leaves before pasteurization has not been reported. This study aimed to find a good combination of tannase (1 mg/ml) and tyrosinase (111; 446; 1785 U/ml) to produce high antioxidant activity of RTD black tea. The results showed that higher tyrosinase concentration decreased the antioxidant activity (DPPH and reducing power), epicatechin (EC), epigallocatechin (EGC), and epigallocatechin gallate (EGCG) content yet increased the theaflavin content and theaflavin (TF)/thearubigin (TR) ratio in the tannase-tyrosinase treated black tea. Still, the highest concentration of tyrosinase (1785 U/ml) in tannase-tyrosinase black tea produces higher antioxidant activities, gallic acid, EC, and EGC content than commercial black tea and tyrosinase without tannase-treated black tea. Thus, the combination of tannase (1 mg/ml) and tyrosinase (1785 U/ml) could be the best treatment to produce high-antioxidant black tea.